The Market Comparisons Appraisal Effect on the Housing Boom Cycles - Keenan, Donald C.; Kim, Taewon; Lee, Daniel C. (Journal of Applied Business and Economics, 2021)
There is a pattern of gradual price rises and noticeably more sudden price drops in the housing market. This is because, in an upmarket, the market comparisons approach of the standard real estate appraisal technique forces home loan underwriters to be reluctant to approve a bigger loan than what the contemporary market comparisons would indicate. On the other hand, in a down market, underwriters do not face any such restriction, and hence prices can drop to the level fully reflecting the declining market condition. The traditional extrapolation typically used to determine the “time” value adjustments needs to be used more cautiously.